Van Siska van Rosemael tot Max Havelaar Receptie van Nederlandstalige literatuur in Tsjechische vertaling tussen 1848 en 1948 - Engelbrecht, Wilken (Lage Landen Studies, 2021)
Migration of literature across regional and national borders is a thriving research topic. This issue of LLS is the first general overview of the reception of Dutch-language literature in Czech translation in the period 1848-1948: of the novels of Conscience, in which similarities were found between the language struggle of the Flemish with their French-speaking elite and the struggle of the Czechs with their German-speaking elite, about literature at the time of both world wars, in the period in between, when Johan Fabricius and Felix Timmermans were authors beloved by Czechs, to the end of the unlimited reception of Dutch-language works by Soviet influences and the norms of the new socialist realism , the Sorela. This fascinating study offers new insights into the influence of Flemish and Dutch works in Europe, but it also examines the parallels between literature, politics and society.